Extreme Stent Malapposition after Percutaneous Coronary Intervention in Bifurcation Lesions: An Optical Coherence Tomography - Refaat, Hesham (Journal of Cardiovascular Medicine and Cardiology, 2020)
Background: Anecdotal cases of bifurcation lesion stenting indicated that a wrong kissing Balloon Inflation (KBI) technique can lead to extreme stent malapposition with even stent crushing. The aim of this study was to quantify the occurrence of this finding, despite achieving acceptable angiographic results. Methods: A total of 229 bifurcation lesions were included in this study. Optical Coherence Tomography (OCT) was obtained immediately after KBI. The stented bifurcation lesions were classified into 2 groups: group 1 with extreme malapposition (malapposition distance ≥ 1mm and in-stent minimal Cross Sectional Area (CSA) <70% of the distal reference CSA), and group 2 (malapposition distance <1mm and/or in-stent CSA >70% of the distal reference CSA). Results: OCT revealed a mean stent malapposition distance of 0.43 ± 0.47 mm extending for a mean length of 1.88 ± 1.82 mm. Forty four cases (19.2%) of extreme stent malapposition were observed, and characterized by a stent malapposition distance of 1.49 ± 0.3 mm. These stents were under-expanded with lower stent eccentricity index (SEI), compared with those without extreme malapposition (48.38 ± 9.67 vs. 60.97 ± 33.29, p=0.46 and 0.57 ± 0.15 vs. 0.74 ± 0.89, p<0.001, respectively). This is mainly attributed to the wrong passage of guide-wires, while performing wire exchange during KBI technique. Conclusion: The bifurcation stenting requiring a KBI technique can be complicated by an extreme degree of stent malapposition; or even stent crushing in some cases, caused by the wrong passage of one or both guide-wires through the stents, during the wire exchange.